Towards Better Simultaneous Interpretation - Wong, Fook Khoon (Journal of Modern Languages, 2017)
This study considers the role of ‘interpretation’ and ‘interpreter’ in conferences. Two types of interpretation services, i.e. simultaneous interpretation and consecutive interpretation are considered as well. Simultaneous interpretation conveys a message into another language (TL) at virtually the same moment in time as it is expressed in the first language. The ‘interpreter’ begins speaking once he has heard a chunk or prepositional phrase in the stimulus passage in the source language (SL) and translates or interprets it simultaneously into his mother-tongue (ML) or target language lagging at most a few seconds behind the speaker.